You Are a Badass Every Day: How to Keep Your Motivation Strong, Your Vibe High, and Your Quest for Transformation Unstoppable - Jen Sincero (New York Viking, 2018)
For anyone who has ever had trouble staying motivated while trailblazing towards badassery, You Are a Badass Every Day is the companion to keep you fresh, grateful, mighty, and driven. In one hundred exercises, reflections, and cues that you can use to immediately realign your mind and keep your focus unwavering, this guide will show you how to keep the breakthroughs catalyzed by Sincero's iconic books You Are a Badass and You Are a Badass at Making Money going. Owning your power to ascend to badassery is just the first step in creating the life you deserve--You Are A Badass Every Day is the accountability buddy you can keep in your back pocket to power through obstacles, overcome the doubts that hold you back from greatness, and keep the fires of determination roaring while you reach your goals.
Keywords: Nonfiction; Motivation; Personal Development; Self Help